Seasonal Variation in Patch Test Results with European Baseline Series - Aïcha Brahem; Haifa Aroui; Asma Gaddour; Asma Chouchene; Asma Aloui; Imen Kacem; Maher Maoua; Houda Kalboussi; Olfa ElMaalel; Souhail Chatti; Faten Dabbabi; Nejib Mrizek (Dermatology Research and Practice)
Aim. To study the influence of season on patch tests results. Methods. We conducted a retrospective epidemiological study which concerned all the patients of the Tunisian center, who consulted in the Dermato-Allergology Unit of Occupational Medicine Department of Farhat Hached University Hospital-Sousse (Tunisia) over a period of 07 years. All the patients were tested by the European Standard Battery allergens (BSE). Results. The data of 1000 patch tests were analyzed during the study period. More than half of the patch tests (58.6%) was positive. In winter, 63% of patch tests showed a positive reaction versus 52% of patch tests in summer without a statistically significant association. However, results of lanolin alcohols, epoxy resin, and Sesquiterpene lactone mix varied significantly with season. Atopy was significantly associated with 18.8% of positive reactions in winter and only with 5.2% of positive reactions in summer (p=0.015). Conclusion. Seasonal variations in patch tests results were more significant with some allergens of European Standard Battery and in atopic patients.